Effect of Corporate Social Responsibility and Good Corporate Governance on the Value of Company with Profitability as Moderating Variables - Ery Yanto, S.E., Ak., M.Ak. (President University Press, 2018)
This research aims to examine the influence of disclosure of corporate social responsibility and good corporate governance on the firm value to profitability as a moderating variable of manufactured companies listed on the Indonesia Stock Exchange for the period 2010-2012. This type of research is an association research using purposive sampling technique. The population in this study are the manufactured companies listed on Indonesia Stock Exchange during the years 2010-2012, as many as 91 companies as selected samples, thus, the total of observations in this study is composed of 273 companies that are analyzed using multiple linear regression with moderate regression analysis. The data used are from financial statements and sustainable report. Hypothesis testing using t test and F test. Research results showed that disclosure of corporate social responsibility and good corporate governance that is moderated affects firm value.